International norms and mechanisms of legal responsibility for acoustic terror - Zakharchuk, R. M. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article provides an interdisciplinary legal analysis of the international responsibility of states for the use of acoustic terror in armed conflicts. Acoustic terror is examined as a method of violence employed to inflict psychological pressure, demoralization, and systematic sleep deprivation of civilians or adversaries. In the context of modern hybrid warfare, the author emphasizes the destabilizing and destructive effect of sound-based attacks. Particular attention is paid to examples of acoustic means used during the Russian-Ukrainian war (since 2022) and Russian military operations in Syria (2015–2020), where airstrikes and shelling created continuous noise exposure affecting the civilian population. The paper argues that although international humanitarian law lacks explicit norms regarding acoustic terror, existing legal mechanisms allow analogies to non-conventional weapons, such as chemical or psychological weapons. The jurisprudence of the International Criminal Court (ICC), the International Court of Justice (ICJ), and the International Criminal Tribunal for the former Yugoslavia (ICTY) is thoroughly reviewed, including cases such as DRC v. Uganda, the Lockerbie bombing, chemical weapons in Syria, and rulings on Karadžić, Milošević, and the shelling of Sarajevo. While none of these cases directly addressed acoustic terror, they establish legal foundations for recognizing such actions as violations of international humanitarian law. The article also highlights the evidentiary challenges in classifying acoustic terror as torture. It proposes improved documentation methods, including psychiatric assessments, acoustic monitoring, and sound impact technologies. The author calls for international standards to assess psychological harm resulting from sonic attacks. In conclusion, the article stresses the urgent need to establish a specialized legal regime to classify acoustic terror as a separate category of war crime or crime against humanity. Specific directions are proposed: codifying the definition of acoustic terror in international instruments, introducing sanction and accountability mechanisms, and creating an international register for documenting sound-based attacks. The study contributes to the evolution of international law by drawing attention to emerging forms of violence within hybrid armed conflicts.